Emotional regulation, attachment style, and assertiveness as determinants of well-being in emerging adults - Plantade-Gipch, Anne; Bruno, Julien; Strub, Lionel; Bouvard, Martine; Martin-Krumm, Charles (Frontiers in Education, 2023)
The emerging adult stage of life is a time of many positive changes, as well as stress and uncertainty. Certain psychological characteristics - such as emotional regulation, attachment style, or assertiveness – could help these adults thrive and maintain positive mental health. This study aimed to explore the influence of these variables on the well-being of emerging adults. The sample included 360 French emerging adults, with a mean age of 21.3 years. Well-being was assessed with the Mental Health Continuum, emotional regulation with the Emotional Regulation Difficulties Scale, assertiveness with the Assertiveness Scale, and attachment with the Relationship Scales Questionnaire. Results showed that emotional regulation, assertiveness, and attachment styles predicted emerging adults' well-being. This study also highlighted the role of substance use and experiences of violence on emerging adults' emotional regulation and well-being. Results support the importance of in-person and distance education and prevention to support emerging adults' well-being, especially in higher education institutions and in times of the COVID pandemic.